Recherches Comparatives d’Ordre International (Cross-National Research). Transactions of the Sixth World congress of Sociology (Actes du Sixième Congrès Mondial de Sociologie). Volume I - Uribe Villegas, Óscar (Revista Mexicana de Sociología, 2020)
No disponible.